Elemental Sulfur Mediated Novel Multicomponent Redox Polycondensation for the Synthesis of Alternating Copolymers Based on 2, 4‐Thiophene/Arene Repeating Units. Issue 6 (26th January 2021) - Mutlu, Hatice; Döpping, Daniel A.; Huber, Birgit; Theato, Patrick
Abstract: A sulfur‐based self‐condensation method is investigated as an efficient tool for the synthesis of polythiophene derivatives. The reaction proceeds through multicomponent redox polycondensation between readily available diketone compounds and elemental sulfur in the presence of a Brønsted acid/base pair. Six different diketone derivatives have been screened and the polymerization is generalized by the synthesis of so‐far‐unprecedented alternating copolymers based on 2, 4‐thiophene/arene repeating units. By exploiting microwave heating the synthetic procedure is optimized, particularly for alternating copolymers containing aryl and thiophene units, such that a copolymer can be synthesized in only 24 h compared to the conventional process taking 6 d, yielding polymers within the same apparent weight average molar mass ( M w ). All obtained copolymers are analyzed in detail using size exclusion chromatography (SEC), nuclear magnetic resonance (NMR), attenuated total reflectance infrared spectroscopy (ATR‐IR), thermal gravimetric analysis and differential scanning calorimetry (DSC). Abstract : A sulfur‐based multicomponent polycondensation is reported for the first time as an efficient tool for the synthesis of unprecedented alternating copolymers based on 2, 4‐thiophene/arene repeating units starting from commercially available raw materials.